Effect of winemaking treatment and wine aging on phenolic content in Vranec wines - Ivanova, Violeta; Vojnoski, Borimir; Stefova, Marina (Springer Science and Business Media LLC, 2012)
Phenolic compounds and colour stability of red wines produced from Vranec Vitis vinifera L. grape variety were investigated by means of different maceration times (3, 6 and 10 days), two doses of SO2 (30 and 70 mg/L SO2), two yeasts for fermentation (Vinalco and Levuline), temperature of storage and time of aging (3, 6 and 16 months). In general, maceration time influenced the phenolics extraction from the grapes into the wine. Highest concentrations of phenolic components were observed in the wines produced with 6 days of maceration, except for the flavan-3-ols which were present in highest amounts in the wines macerated for 10 days. Higher doses of SO2 increased the extraction of polyphenols, preventing the wines from oxidation, while the effect of yeast on phenolics extraction was not significant. Wine aging affected the phenolic content of wines produced with 3 days of maceration and caused intensive decrease of anthocyanins during the storage period. Wines aged at higher temperature showed lower anthocyanin levels and less intense coloration. Principal component analysis revealed that separation of the wines was performed according to the hue value in correlation with the maceration time and time of wine aging.